Relationship Between the Use of Topical Hypothermia with Ice Water to Postoperative Pulmonary Complications of Coronary Artery Bypass Graft - Agustina, Sri; Gama Satria; Erial Bahar (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2024)
Introduction: Open heart surgery such as coronary artery bypass graft (CABG) is a heart surgery technique that uses a machine cardiopulmonary bypass (CPB) which can cause postoperative complications such as systemic inflammatory response syndrome (SIRS) and myocardial damage. Myocardial protection can be achieved through topical hypothermia techniques by lowering the heart temperature using a cold solution or ice cubes. Although several studies have shown its benefit in protecting the myocardium, the use of topical hypothermia remains controversial due to its uneven cooling effect and risk of tissue injury. This study aims to evaluate the relationship between the use of topical hypothermia of ice water and pulmonary complications of open heart surgery. Methods: This research is an analytical observational cohort retrospective comparison of pulmonary complications postoperatively in cardiac surgery patients who received systemic cardioplegia alone versus those who received a combination of systemic cardioplegia and topical hypothermia. Data collection was carried out using techniques consecutive sampling. Results: Of the 32 research subjects, the results of the analysis showed that the use of topical hypothermia did not have a statistically significant relationship (p>0.05) on the incidence of leukocytosis, pulmonary edema, duration of surgery, duration of ventilator use, duration of hospitalization, and mortality compared to the group that only received systemic cardioplegia. There was a significant relationship (p<0.05) between the incidence of pleural effusion in the topical hypothermia group. Conclusion: The use of topical hypothermia in cardiac surgery has a significant association with a higher incidence of pleural effusion.